Ethnobotany of the Gitksan Indians of British Columbia - Smith, Harlan I., 1872-1940 (Mercury series., 1997)
During the 1920s Harlan I. Smith, an archaeologist with the National Museum of Canada, documented plant and animal knowledge and use among the Gitksan, Nuxalk and Ulkatcho Carrier of British Columbia. This volume is an edited version of a manuscript by Smith, which contains information on 112 botanical species and their traditional cultural roles among the Gitksan. Prepared between 1925 and 1927, Smith's work is the earliest, relatively comprehensive ethnobotanical study for any Tsimshianic group, the first record of a clearly ethnobotanical investigation undertaken in British Columbia, and the first to include the term "ethnobotany" in its title. This thoroughly revised version of the manuscript also offers additional introductory text, ethnobotanical and linguistic commentary, and concluding remarks not found in the original.